ChemInform Abstract: Reactivity of Carbon Dioxide in Hydrofluoroethers: A Facile Access to Cyclic Carbonates. Issue 50 (December 2015) - Mamone, Marius; Milcent, Thierry; Crousse, Benoit
Abstract: The high solubility of CO2 in hydrofluoroethers provides access to various cyclic carbonates (III) with excellent selectivities and yields.